Multi-objective robust optimization method for multi-agent collaborative platform production task planning - TAI JIANWEI; WU ZHIWEI; LI XIAODUO; TIAN YAJING; CHEN YINGYING; LUO HE; WANG GUOQIANG; WANG DI; LIN HAOSHENG; ZHU JIAWEI (2023)
The invention provides a multi-objective robust optimization method and system for multi-agent collaborative platform production task planning, a storage medium and electronic equipment, and relates to the technical field of multi-agent collaborative platform production task planning. The method comprises the following steps: firstly, according to production task planning resources and single-batch overseas orders of the multi-agent collaborative platform, on the premise of determining the shipping time, constructing a production task planning model taking a manufacturing enterprise body as a core; and then designing an infinity norm sphere uncertainty set for ship shipping time, constructing a robust square multi-objective model of cross-region multi-subject production task planning, and optimizing multiple objectives of total delivery time deviation and total delivery cost of a single batch of overseas orders. According to the model, a marine transportation plan made by a shipping company main body in advan